2003
DOI: 10.1029/2003jb002527
|View full text |Cite
|
Sign up to set email alerts
|

Toggling of seismicity by the 1997 Kagoshima earthquake couplet: A demonstration of time‐dependent stress transfer

Abstract: [1] Two M $ 6 well-recorded strike-slip earthquakes struck just 4 km and 48 days apart in Kagoshima prefecture, Japan, in 1997, providing an opportunity to study earthquake interaction. Aftershocks are abundant where the Coulomb stress is calculated to have been increased by the first event, and they abruptly stop where the stress is dropped by the second event. This ability of the main shocks to toggle seismicity on and off argues that static stress changes play a major role in exciting aftershocks, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(179 citation statements)
references
References 32 publications
(48 reference statements)
4
173
2
Order By: Relevance
“…In fact, isolating the immediate San Simeon aftershock zone defined by (somewhat arbitrary) spatial limits 35.35°-35.9°N and 121.2°-120.65°W, one finds an apparently abrupt decrease in seismicity at the time of the Parkfield mainshock ( Figure 6). The result shown in Figure 6 is reminiscent of the "toggling" of seismicity observed by Toda and Stein (2003) and, more fundamentally, the stress shadow hypothesis (e.g., Harris and Simpson, 1992;Jaume and Sykes, 1996). Such an effect would presumably be related to the static stress change caused by the Parkfield mainshock in the San Simeon region, an issue well beyond the scope of this paper.…”
Section: Triggered Earthquakes Following Parkfieldmentioning
confidence: 80%
See 2 more Smart Citations
“…In fact, isolating the immediate San Simeon aftershock zone defined by (somewhat arbitrary) spatial limits 35.35°-35.9°N and 121.2°-120.65°W, one finds an apparently abrupt decrease in seismicity at the time of the Parkfield mainshock ( Figure 6). The result shown in Figure 6 is reminiscent of the "toggling" of seismicity observed by Toda and Stein (2003) and, more fundamentally, the stress shadow hypothesis (e.g., Harris and Simpson, 1992;Jaume and Sykes, 1996). Such an effect would presumably be related to the static stress change caused by the Parkfield mainshock in the San Simeon region, an issue well beyond the scope of this paper.…”
Section: Triggered Earthquakes Following Parkfieldmentioning
confidence: 80%
“…The association of triggered earthquakes with dynamic stress changes is in contrast to aftershocks, which have been assumed to be caused primarily by local, static stress changes associated with fault movement (e.g., Das and Scholz, 1981;King et al, 1994;Toda and Stein, 2003). (According to convention, aftershocks are generally, albeit vaguely, assumed to be events within one to two fault lengths of a mainshock.)…”
Section: Remotely Triggered Earthquakesmentioning
confidence: 99%
See 1 more Smart Citation
“…For application of the rate-and-state friction model, previous studies (e.g., Toda and Stein 2003;Toda et al 2005;and Catalli et al 2008) suggested that the physically reasonable range for Aσ was between 0.1 and 0.4 bars. In this study, a fixed Aσ of 0.2 bars was assumed.…”
Section: The Short-term Seismicity Rate Changementioning
confidence: 99%
“…Whereas CPT is designed for changes in normal stress by changing pore pressure, Dieterich (1994) derives a general equation for seismicity changes, as compared to the background seismicity if shear and/ or normal stresses are changed. The RST has been used in the simulation of aftershocks and earthquake swarms (Catalli et al 2008;Daniel et al 2011;Dieterich et al 2000;Kilb et al 2002;Toda et al 2002Toda et al , 2003 and recently also utilized for seismicity modelling in geothermal reservoirs (Hakimhashemi et al 2014). In this model, the change in Coulomb failure stress (King 2007) is combined with the RST theory.…”
mentioning
confidence: 99%